Implementation of Eco-Office by Guest Service Division in Supporting Melia Bali a s a Green Hotel - Wedarianti, Luh Made Putri; Darlina, Lien; Nugraha, Putu Virgananta; Dyah, Wahyuning; Wijaya, I Nyoman Cahyadi (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This research aims to determine the implementation of eco-office by Guest Service Division in supporting Melia Bali Indonesia as a green hotel. Research method: The data collection method used in this research is observation, questionnaires, interviews and documentation. Researchers conducted interviews with the guest service manager & assistant manager and distributed questionnaires to the five guest service division staff. The data analysis technique used is qualitative descriptive analysis with descriptive statistics ranging from rating scales in the form of averages. Results and discussion: The results of the analysis show that Melia Bali Indonesia, especially the guest service division, adopts the eco-office concept which is divided into 5, namely electricity saving aspects, water saving & conservation aspects, office waste management aspects, greening aspects, and Other aspects of efforts made in addition to the previous criteria are related to maximizing the use of technology as a means of communication and making reports, as well as minimizing the use of paper and plastic. Implication: The implementation of eco-office has been carried out quite well, so that these efforts directly contribute to the hotel's efforts to implement the green hotel as a whole.